Virus- vector relationship of yellow vein disease of calendula and the whitefly (The Journal of Plant Protection Sciences, 2021)
Virus causing yellow vein disease on Calendula officinalis L. was transmitted from naturally infected C. officinalis to  healthy seedlings of C. officinalis through whiteflies not through sap inoculation. A single whitefly could transmit the  virus and showed 20.55% infection and fifteen whiteflies were required for 100 percent transmission. The minimum  acquisition access feeding period and minimum inoculation access feeding period for the present virus were 10min and  30min, respectively. Acquisition access feeding period and inoculation access feeding period was 100 percent at 6hr and  3 hr respectively. A pre-acquisition access feeding period of 3hr or more gave 100 percent transmission. Post acquisition  access feeding period of whiteflies did not have any effect in increasing transmission of CYVV. As post acquisition  access feeding period increased, the transmission of CYVV was gradually decreased.
Keywords: Whitefly; Calendula; Yellow vein disease; Transmission